#TITLE_ALTERNATIVE# - SIDARGO (NIM : 10212059), MUHAMMAD
Since industrial revolution, earth's atmospheric temperature increases significantly. Many theory have been developed to answer that question. One of the most significant is the impact of Carbon Dioxide. It appears that increasing carbon dioxid straightly related to the increasing earth's atmospheric temperature. In order to reduce production of carbon dioxide, we need to reconsider of electricity production sector. Nuclear Power Plant (NPP) is one of the realistic option to produce electricity with still maintaining environmental aspect, especially the quality of air. In this study, Small Pb-Bi Cooled Non-Refueling Nuclear Power Reactor (SPINNOR) is used as the design. SPINNOR is one of the Fast Reactor Spectrum that uses Pb-Bi as a coolant. This design targets long lasting operation as its main objective. Long lasting operation of reactor can be achieved by using variation of Uranium enrichment inside the core. Low-enriched fuel were placed in the central core. It contained high fertile material which be can transformed into fissile material. Whereas high enriched fuel were placed near the outer core. By this configuration burn-up was focused on the outer core at the Beginning of Life (BOL), while at the End of Life (EOL) burn-up was focused on the central core. This study used Standard Reactor Analysis Code (SRAC) to solve numerical solution. Uranium(233)-Thorium(232) were used as fuel. Neptunium-237 needed to attain excess reactivity level under 1 percent. Optimum design obtained when Uranium-233 enrichment level was 7.6%, 8.2%, and 8.4% with 4% addition of Neptunium-237. All said composition and configuration would result in excess reactivity level under 0.5%.